Atomic Softness and Its Application in Site Selectivity of Antimitotic Natural Products - Pandey, P.P.; Gupta, A.K.; Singh, P.P. (Asian Journal of Chemistry, 2010)
The reactive sites of 19 natural product drugs having anticancer property have been identified. The site having the highest value of the descriptors except the ionization potential have been chosen as possible site through which the drug interferes with the dynamics of tubulin. The values so chosen have been used for QSAR model. 17 QSAR models have been found to have reliable predictive power. The best among them is the model obtained by using the combination of descriptors the highest softness En‡, the lowest ionization potential, the highest electron affinity and the highest density distribution function.